2020
DOI: 10.1103/physrevb.102.245153
|View full text |Cite
|
Sign up to set email alerts
|

Oxide Fermi liquid universality revealed by electron spectroscopy

Abstract: We present a combined soft x-ray and high-resolution vacuum-ultraviolet angle-resolved photoemission spectroscopy study of the electron-overdoped cuprate Pr 1.3−x La 0.7 Ce x CuO 4 (PLCCO). Demonstration of its highly two-dimensional band structure enabled precise determination of the in-plane self-energy dominated by electron-electron scattering. Through analysis of this self-energy and the Fermi liquid cut-off energy scale, we find-in contrast to hole-doped cuprates-a momentum isotropic and comparatively wea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
2
4
0
Order By: Relevance
“…Note that for a given threshold, all dopings of the left panel here fall on the same straight line, with only small variations. a 2 coefficient in the electron-doped cuprate PLCCO is constant as a function of the Fermi-surface angle in the overdoped regime [8]. These measurements are reminiscent of our results at x = 0.25, far from the AFM QCP.…”
supporting
confidence: 83%
See 4 more Smart Citations
“…Note that for a given threshold, all dopings of the left panel here fall on the same straight line, with only small variations. a 2 coefficient in the electron-doped cuprate PLCCO is constant as a function of the Fermi-surface angle in the overdoped regime [8]. These measurements are reminiscent of our results at x = 0.25, far from the AFM QCP.…”
supporting
confidence: 83%
“…Horio et al [8] also suggested a spectroscopic analog of the Kadowaki-Woods ratio that would relate a 2 and Z, two quantities we obtained in our calculations for multiple values of U . This is discussed in Fig.…”
supporting
confidence: 63%
See 3 more Smart Citations